1041 ELECTROCARDIOGRAPHIC HETEROGENEITY OF PATIENTS WITH VARIANT TRANSTHYRETIN AMYLOID CARDIOMYOPATHY: GENOTYPE PHENOTYPE CORRELATIONS. (15th December 2022) - Russo, Domitilla; Cappelli, Francesco; Di Bella, Gianluca; Tini, Giacomo; Porcari, Aldostefano; Cipriani, Alberto; Canepa, Marco; Merlo, Marco; Licordari, Roberto; Vianello, Pier Filippo; Zampieri, Mattia; De Michieli, Laura; et al.
Abstract: Transthyretin (TTR) amyloid cardiomyopathy due to mutation on TTR gene (vATTR) has extremely different features according to the type of mutation, ranging from a mild to an extensive cardiac involvement. Data about electrocardiographic findings (ECG) in vATTR are limited and not informative of genotype correlation. Aim of this study is to analyze ECG characteristics and their correlation to clinical and echocardiographic aspects in patients with vATTR cardiomyopathy, focusing on different TTR mutations. This is a multicentric, retrospective, observational study performed in six Italian referral centres for cardiac amyloidosis. We divided patients in two groups, according to the previously described phenotypic manifestations of the TTR mutation. Of 64 patients with vATTR cardiomyopathy, 23 (36%) had prevalent cardiac (PC) TTR mutations and 41 (64%) patients had a prevalent neurological (PN) TTR mutations. Patients with PC mutations were more frequently males and older, with advanced NAC staging. At baseline ECG, atrial fibrillation was more common in patients with PC, while pacemaker induced rhythm in those with PN mutations. Prevalence of atrioventricular and intraventricular blocks, pseudonecrosis pattern and low voltages were not significantly different in both groups. PQ and QRS durations were longer and voltage to mass ratio was lower in PC mutations. Different TTR mutations tend to have distinctive ECG features. The standard ECG in vATTR is extremely heterogeneous and the specific mutations are associated with distinct instrumental and clinical features. The differences between PN and PC vATTR are only partially explained by the different degree of cardiac infiltration.